PROSES PENGAMBILAN MINYAK ATSIRI DARI TANAMAN NILAM (Pogestemon cablin Benth) MENGGUNAKAN METODE MICROWAVE HYDRODISTILLATION - Yuliana, Dwi Astri; urhidayati, Siti; ., Zurohaina; Aswan, Arizal; Febriana, Ida (Politeknik Negeri Sriwijaya, 2020)
Patchouli essential oil that is produced using conventional refining technology often does not meet the requirements for export. Refining using conventional technology requires a relatively long time, the energy required is large and the product quality is low. To improve the quality of patchouli oil and energy savings in this study, the process of making patchouli oil using the Microwave hydro distillation method is used. This process is a combination of the use of microwaves with a distillation system. The material in the flash column section which is made of glass will be penetrated by microwave radiation and will be absorbed by the material. This event will cause heat so that the cell walls in the oil will break and the content in the oil will be free to escape. Based on the results of the study using patchouli plant raw materials, the optimal variation in operating time and microwave power to obtain high yields at 60 minutes power was 0.3301% and the lowest SEC value was at 30 minutes power which was 1.889.92 gr / ml. While the results of the study used patchouli leaf raw materials, the optimal variation in operating time and distillation temperature to obtain high yields at a temperature of 98ËšC minutes 60, namely 0.3301% and the lowest SEC value at a temperature of 98ËšC minutes 30. which is 1,889.92 gr / ml.